Electronic Anisotropy at Vicinal Ag(1 1 n) Surfaces: Energetics of Hydrogen Adsorption - Juarez, Maria Fernanda (2016)
We have investigated the adsorption and diffusion of hydrogen atoms at planar (1 0 0), (1 1 1), and stepped (1 1 n) silver surfaces by density functional theory. At low coverage, hydrogen atoms tend to adsorb on step sites rather than on the terrace. The adsorption energy for hydrogen on steps stays almost the same for all (1 1 n) surfaces, showing the local character of the orbitals on these sites. However, the situation is different on the terrace. The adsorption depends on both the position and the length of the terrace. The stability of hydrogen is higher on the middle of the terrace. In contrast to the planar (1 0 0) surface, the adsorption energy decreases when the coverage on the steps increases. Small activation barriers for the up- or downward diffusion show that hydrogen atoms can reach the steps easily at room temperature.